PRE-TRIAL: THE SUSPECTS' ULTIMATE WEAPON AND CORRECTION TOOL FOR INVESTIGATORS TO BE MORE PROFESSIONAL FROM THE PERSPECTIVE OF LEGAL EXPEDIENCY - Albertus Luter; Ramlani Lina Sinaulan; Mohamad Ismed (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to determine the practice of holding pretrial hearings in Indonesia changed in the aftermath of the 2014 constitutional court ruling 21 / PUU-XII / 2014 as well as legal expediency accrue from pre-trial actions against suspects' determinations, both for the suspect himself and for the suspect. This study is a descriptive qualitative research with the use of normative legal research with primary data collection namely Court Decisions, Legislations which are analyzed using Legislative approaches, Case Approaches and Analytical Approaches. The findings reveal that Pretrial hearings were implemented in Indonesia following the constitutional court's decision Number: 21 /PUU-XII/2014, creating a new legal phenomenon in which suspects flocked to file pretrial legal efforts, which naturally clogged up relevant state institutions such as POLRI, KPK, the Prosecutor's Office as well as the District Court, where pretrial which had previously been viewed as a less popular legal effort, was instantly weakened as if it Advocates defending suspects and on the other hand, related institutions can prepare themselves by enacting a series of regulations requiring increased prudence in determining suspects in order to "survive" the new weapons of suspects known as Pretrial. However, when viewed through the lens of legal expediency, it is a positive thing for investigators because it means that Pretrial can be used as a tool of correction.